2016
DOI: 10.1021/acs.organomet.6b00744
|View full text |Cite
|
Sign up to set email alerts
|

X–H Bond Activation on Cr(III),O Sites (X = R, H): Key Steps in Dehydrogenation and Hydrogenation Processes

Abstract: We synthesized isolated Cr­(III) sites on SiO2−Al2O3 and Al2O3 by grafting and subsequent controlled thermal treatment of Cr­(OSi­(OtBu)3)3(THF)2 and Cr­(Al­(OiPr)4)3 on alumina. CrO x /Al2O3 was obtained from incipient wetness impregnation of Al2O3 with CrO3 in H2O followed by calcination, as carried out for the synthesis of industrial Cr-based dehydrogenation catalysts. These materials were characterized by IR, EPR, XAS, and by the adsorption of the probe molecules CO and pyridine, and the results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 70 publications
(38 reference statements)
2
60
0
6
Order By: Relevance
“…[89] Calculations performed on Cr III /SiO 2 also suggest that b-alkyl elimination from an M-propyl intermediate can lead to ethylene and methane-the cracking products. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site.…”
Section: Non-oxidative Dehydrogenationmentioning
confidence: 98%
See 4 more Smart Citations
“…[89] Calculations performed on Cr III /SiO 2 also suggest that b-alkyl elimination from an M-propyl intermediate can lead to ethylene and methane-the cracking products. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site. [89,91,93,94,96] Para-hydrogeninduced polarization (PHIP) experiments for Cr and Co have indicated that p-H 2 could be incorporated into propene in ap airwise fashion, consistent with the hydrogenation and dehydrogenation involving heterolytic H À Ha nd C À Hs plitting at an M À O site.…”
Section: Non-oxidative Dehydrogenationmentioning
confidence: 98%
“…[88,89] Achromium aluminate material free of surface Si sites, Cr-2/Al 2 O 3 ,has also been prepared by the grafting of Cr(k 2 -Al(OiPr) 4 ) 3 (Cr-2)o nto Al 2 O 3-700 followed by thermal treatment at 400 8 8C( Scheme 2d). [89] Similarly,monomeric Ga III [90] and Co II [91] sites supported on silica have also been prepared by using this approach (Scheme 2). Thep resence of monomeric sites was established through av ariety of spectroscopic techniques,i ncluding aW avelet transform analysis of the EXAFS data.…”
Section: Non-oxidative Dehydrogenationmentioning
confidence: 99%
See 3 more Smart Citations